UNDERSTANDING NEW LANGUAGE: MUTUAL INTELLIGIBILITY IN ROMANCE LANGUAGE PAIR - Diana Oktavia (Universitas Muhammadiyah Muara Bungo, 2019)
This paper concerns to the strategy applied by speakers of mutual intelligibilitity languages pairs in Europe, especially in Romance language pair, Portuegese and Spanish. Initial studies found a receptive multilingulism as a great strategy to break the gap of communication within these two languages. It is found that the speakers of both Portuegese and Spanish are able to communicate and understand each other even though they do not speak each other language. It happens because those two languages resemble each other and they have a large number of cognate words which makes them recognizable. However, it is also found that Portuegese speakers can understand Spanish easier than Spaniards understand Portuegese, because Portuegese is more complicated than spanish.